Examining Teacher Absenteeism and the Role of School Heads in Attendance Monitoring in Kinondoni Municipality - Sanga Magreth; Prospery M. Mwila (PT. Pusmedia Group Indonesia, 2025)
Teacher absenteeism is a critical issue affecting the quality of education in Tanzania, particularly in secondary schools. This study explores the nature, frequency, and underlying causes of teacher absenteeism in Kinondoni Municipality, with a focus on the role of school heads in monitoring and managing attendance. Using a mixed-methods approach, data were collected from 120 teachers, 20 school heads, and 10 education officers through structured questionnaires, interviews, and document analysis. The study employed a sequential explanatory design, wherein quantitative data were analyzed using SPSS to identify trends in absenteeism, while qualitative responses underwent thematic analysis to explore deeper insights into the reasons behind absenteeism.The findings reveal that absenteeism is widespread, with 60% of teachers reporting being absent at least twice a week. The main causes include health issues, family responsibilities, and excessive administrative duties. Inadequate leave policies and poor working conditions were also highlighted as contributing factors. The study further found that only 40% of schools had structured systems for tracking attendance, and many school heads expressed challenges in enforcing attendance policies due to limited support from education authorities. Based on these findings, the study recommends strengthening accountability measures through clearer and more flexible attendance policies, the implementation of digital attendance tracking systems, and enhanced leadership training for school heads. Additionally, improving teacher welfare by addressing workload, health, and professional development is crucial in reducing absenteeism. These measures are essential for fostering a more committed teaching workforce and improving educational outcomes in the region.